If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + -9) = 33 Reorder the terms: (-9 + 2x) = 33 Remove parenthesis around (-9 + 2x) -9 + 2x = 33 Solving -9 + 2x = 33 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + 2x = 33 + 9 Combine like terms: -9 + 9 = 0 0 + 2x = 33 + 9 2x = 33 + 9 Combine like terms: 33 + 9 = 42 2x = 42 Divide each side by '2'. x = 21 Simplifying x = 21
| e*779942286= | | -5+3x=9 | | 3x^2+4x=15+y | | 3(x-4)+5=14 | | 4z+3(5-z)=-(z-1)+12 | | 5x-3x=10+3x-3x | | 4(z^2+z-2)=-2z^2-7z+2 | | 12345678*87654321=1 | | 14=-4x-6 | | 52-9x=2x+19 | | 4(z^2+11z-2)=-2z^2-7z+2 | | 9-45+8*4=778*x | | .33x+.67x=10 | | 100P=2400 | | 3=-6x-9 | | 3.5x-1.5x=18 | | .07x=1.4 | | 2w(-6-1)= | | 20x^2-27x=14 | | 2x+9=29-3x | | 58-7x=29x+18 | | t^2-t+1=0 | | 4x+5=6x-7 | | x^2-5xy+4y^2=0 | | 3x*(-5xy)=a | | 5x-4(x-7)=4+2x | | 99+m^2=0 | | 7x+8y-9z=6 | | 13x+13=62-4x | | 14x=-7 | | -35=5y | | -20=-5y |